Den latinamerikanske venstrefløj efter den Kolde Krig - Cancino Troncoso, Hugo (Arbejderhistorie - tidsskrift for historie, kultur og politik, 2012)
Hugo Cancino Troncoso: The Latin American left wing after the Cold War, Arbejderhistorie 3/2012, pp. 54-70. Throughout the 20th century Latin America was the setting for revolutions and bloody state coups. Today the left is split on the questions of globalisation, modernisation, neoliberalism, and the changing of society. In this article there is an analysis of the Latin American left as situated in the new world order emerging at the end of the Cold War with the disintegration of the Soviet bloc in 1992 and up until today. The different reactions and solutions to the national and continental challenges faced by the left are critically accounted for. Either the left wing can accommodate to the new reality, as characterised by globalising and modernising processes, neo-liberalism, new ethnic and social movements, or it can challenge the existing system with a political platform of radical reform. At this moment the left is in power in many countries in Latin America and the article therefore explores the ideological and political foundations of the programmes on which the left variously rules and finally looks at the prospects of a unification of the divided left.